The “Newtonian dream” of Guyton de Morveau - Mocellin, Ronei Clécio (Circumscribere International Journal for the History of Science, 2011)
How to turn chemistry into an exact science? For chemist Louis-Bernard Guyton de Morveau (1737-1816), the best procedure to achieve this goal was to use resources from theoretical physics as allies in the general delimitation of concepts belonging to that science. Thus, their results could be represented in a rational way and written in mathematical language. His dream was to produce concepts that could translate the dynamics of the material world through this physical chemistry. The key-concept of this dream was that of chemical affinities. In addition to information relevant to understand the meaning of being a Newtonian in the Age of Enlightenment, Guyton de Morveau’s chemical thinking also suggests an alternative understanding of the so-called "chemical revolution".